Current Problems and Prospects for the Development of State Control (Supervisory) Bodies in Russia - O. A. Astakhova; V. P. Gridnev (Управленческое консультирование, 2024)
The article examines the peculiarities of the functioning of state control (supervisory) bodies in the Russian Federation at the present time. The subtleties of the mechanism for evaluating the effectiveness of the functioning of the system of control (supervisory) bodies are analyzed using the example of evaluating the work of these bodies in the field of social services in St. Petersburg. The current problems of the functioning of the system of state control (supervisory) bodies in the Russian Federation are reflected. Based on the identified problems, the authors propose a set of measures based on the principles of legality and transparency, a balance of interests aimed at achieving the most useful result for all participants in control (supervisory) activities. The implementation of the proposed measures should follow the path of using modern approaches to managing the system of control (supervisory) bodies based on the results of scientific and technological progress.